Psychological Reflection in Clara Reeve’s novel "The exiles; or, Memoires of the Count de Cronstadt" (Proceedings of Southern Federal University. Philology, 2018)
Elena V. Grigorieva (Rostov-on-Don, Russian Federation)The article focuses on the new types of protagonists that Clara Reeve introduces in her novel «The Exiles, or Memoirs of the Count de Cronstadt». For Reeve, this book was a turning point towards a new genre, the sentimental novel, which was gaining popularity in the late XVIIIth century. No wonder attempts were made to link this novel with numerous literary sources. Epistolary in form, «The Exiles», however, shares genre traits with a memoir (infinitely long, for a whole and a half volumes, a confession letter of the Count of Kronstadt to his friend Berkeley in which the character tells the story of his own life and delusions – a novel in the novel) and a diary and epistolary diary (dated Berkeley de Courville letters – a detailed and consistent account of attempts to save the Count and settle his affairs, also a novel in the novel). The protagonists become the subject of a detailed psychological study. The psychological conflict progresses in a sequence of increasingly precarious compromises. Of special note is the author’s use of national identity concepts: the protagonists embody many national stereotypes that the Enlightenment supported. The character of Count de Cronstadt, a German, becomes the centerpoint for the psychological dimension of the novel. Here Reeve outgrows her previous static psychological portrayal and deconstructs the ‘sentimental hero’ cliché by adding mental and emotional complexity and ambiguity that are more readily associated with the pre-Romantic characters and their controversial selfconsciousness that is in conflict with the linear rationality.Key words: sentimental Gothic, national stereotypes, memoir, psychology, pre-Romanticism, rationality, epistolary novel, introspection.DOI 10.23683/1995-0640-2018-3-149-157